CUIDADOS DE ENFERMAGEM AO PACIENTE COM LESAO RENAL CRÔNICA - Valentini, Cleone Gabriela; Bandeira, Luara Renner; De Souza, Tainá Caroline Gonçalves; Trindade, Letícia Flores; Fernandes Stumm, Eniva Miladi (Salão do Conhecimento, 2018)
Resumo expandido realizando durante o curso de enfermagem da Unijui